Senam Hipertensi Sebagai Upaya Menurunkan Tekanan Darah Penderita Hipertensi - Siswati Siswati; Heni Maryati; Supriliyah Praningsih (Journal Of Health Science (Jurnal Ilmu Kesehatan), 2021)
Introduction: The prevalence of hypertension in indinesia at age > 18 years is 34.11%. according to WHO, people with hypertension who make efforts to control blood pressure are only one-fifth of all sufferers in the world. Hypertension control can be done by controlling risk factors, namely by consuming healthy foods, reducing the amount of salt in food, not consuming alcohol, not smoking, controlling stress, and doing physical activity. Methods: The type of study was one group pre test post test design. The population of this study were hypertension sufferers in Brambang Village. The research sample was 30 respondents with the criteria of hypertension grade 1 hypertension grade 2. The sampling technique used total sampling. Blood pressure data is obtained by measuring blood pressure using digital blood pressure. Results: blood pressure before the intervention was 70% hypertension grade 1 and 30% hypertension grade 2. This data decreased after the intervention with data distribution of 26.7 pre hypertension, 53.3% hypertension grade 1, and 20% hypertension grade 2. Wilcoxon signed rank test statistic showed significant value (p) = 0.000. Conclusion: hypertension exercise that is done regularly and seriously can have a positive impact on stable blood pressure. Keyword: hypertension exercise; blood pressure.